A study on factors that influence the work life balance policies on employee job satisfaction among employees at Nestlé in Mutiara Damansara / Stacy Jungin @ Juggin - Jungin @ Juggin, Stacy (Faculty of Business and Management, 2018)
Work-life balance is now an important determinant for more workers in attaining a thriving career. With increased responsibilities in the work place, the divide between work life and private life has taken on superior significance and entails more consciousness. The stipulations of work or personal life can cause stress and lead to employees turn over. Such circumstances impact on workers physiologically and psychologically. Hence, it is crucial for employees to maintain a sturdy stability between work and their private lives. For the employers, work-life balance of employees is a central means in formulating appropriate strategies to tackle work-life imbalance concerns. This paper studies influence of work life balance policies on employee job satisfaction among employees at Nestlé, Mutiara Damansara It explores the connection between work life balance policies and organizational productivity and whether work life balance policies increase employees job satisfaction through four independent variable which are flexibility policies, leave provision, welfare policy and job design. Work-life balance it is not a quandary to be determined once but a constant concern to be managed. For organization goals to be achieved through the people employed, work-life balance concerns must become a crucial feature of human resource policy and strategy.